Analysis of academic gaps between LPBA and non-LPBA graduates in the English department Higher Education - Moh Nunung Sanjaya; Mohammad Sofyan Adi Pranata (Tamaddun Life, 2026)
This study aimed to identify the academic gap between students in the English Department who graduated from LPBA and those who did not. Differences in previous English learning experiences may influence students’ academic readiness, particularly in speaking, academic reading, and academic writing. This study employed a qualitative comparative design involving six actively enrolled students selected through purposive sampling, consisting of three LPBA graduates and three non-LPBA students. Data were collected through semi-structured interviews exploring students’ learning experiences, perceptions of their academic abilities, and challenges encountered during the learning process. The data were analyzed using thematic analysis through data reduction, theme identification, and conclusion drawing. The findings revealed that the academic gap was shaped by both internal and external factors. Internal factors included self-confidence, learning habits, and academic adaptation, while external factors comprised previous educational background, learning environment, language exposure, and institutional support. LPBA students generally demonstrated greater confidence and stronger communicative competence, whereas non-LPBA students showed better familiarity with text-based academic tasks. Overall, the academic gap reflects the influence of different educational backgrounds and learning experiences on students’ academic readiness.